Virtually you : the dangerous powers of the e-personality - Aboujaoude, Elias, 1971- (New York : W.W. Norton, 2011)
Whether sharing photos or following financial markets, many of us spend a shocking amount of time online. While the Internet can enhance well-being, Elias Aboujaoude has spent years treating patients whose lives have been profoundly disturbed by it. Part of the danger lies in how the Internet allows us to act with exaggerated confidence, sexiness, and charisma. This new self, which Aboujaoude dubs our "e-personality," manifests itself in every curt email we send, Facebook "friend" we make, and "buy now" button we click. Too potent to be confined online, however, e-personality traits seep offline, too, making us impatient, unfocused, and urge-driven even after we log off. This first scrutiny of the virtual world's transformative power on our psychology shows us how real life is being reconfigured in the image of a chat room, and how our identity increasingly resembles that of our avatar.--From publisher description.
E-personality -- Delusions of grandeur -- Narcissism -- Ordinary everyday viciousness -- Impulsivity -- Infantile regression and the tyranny of the emoticon -- Love and sex recalibrated -- The illusion of knowledge -- Internet addiction -- The end of privacy -- Marking time, making memories -- "Virtualism," or the art of being more real than real.
Includes bibliographical references (p. [295]-328) and index.
Keywords: Internet addiction; Internet -- Psychological aspects; Internet -- Social aspects; Personality disorders; Behavior, Addictive -- psychology; Attitude to Computers; Impulsive Behavior -- psychology; Internet -- utilization; Psychosocial Deprivation